PENGARUH ORGANISASI PEMBELAJARAN DAN MANAJMEN PENGETAHUAN TERHADAP KINERJA PEGAWAI BADAN PENGELOLA KEUANGAN DAN ASET DAERAH PROVINSI SULAWESUI TENGAH - Hidayat, Rahmat (Katalogis, 2017)
The study intends to determine and analyze simultaneous and partial influence of learning organization and knowledge management on the performance of officials in the Agency of Financial and Regional Assets Management. The study uses quantitative desciptive approach that show relationship between variables and select all officials in the office if financial and regional assets of 141 people, as respondents by census method. Data is analyzed by using multiple regressions analysis. The results show that learning organization and knowledge management significantly have simultaneous and partial influence on the performance of officials’ in the office of Financial And Regional Assets Management, Central Sulawesi.